Nutritional and antioxidant properties and their inter-relationship with pod characters in an under-exploited vegetable, Indian bean (Lablab purpureus) - RAI, NAGENDRA; RAI, KRISHNA KUMAR; TIWARI, GARIMA; KUMAR, SANJEEV (The Indian Journal of Agricultural Sciences, 2014)
Indian bean [Lablab purpureus (L.) Sweet] is an underexploited nutritious legume vegetable found in tropical regions of Asia and Africa. The nutritional and anti-oxidant properties of 21 pole type Indian bean genotypes were analysed in edible pods in terms of protein, sugar, chlorophyll, carotenoids, phenol, and proline contents. The analyses revealed a significant genotypic variation in the level of protein (102-635.6 mg), sugar (0.188-1.11 mg), chlorophyll (0.121-0.716 mg), phenol (1.7-9.67 mg), proline (0.02-7.06 µg) and carotenoids (0.04-0.231 mg). Estimation of genetic variability parameters revealed that chlorophyll a and non-reducing sugar had high estimates of PCV than GCV, whereas, protein, phenol, chlorophyll b, carotenoid, reducing sugar and non-reducing sugar had moderately high PCV than GCV indicating that such variability could be exploited for successful identification of genotypes for the specific biochemical property. In general, heritability estimates were recorded to be high for all the characters studied except chlorophyll a and reducing sugar. High heritability coupled with high genetic advance as percentage of mean was observed for proline, non-reducing sugar, chlorophyll a, carotenoidd, protein and phenol. Since such traits are controlled by additive genes, more importance need to be given to these traits while selecting the breeding lines rich in nutritional qualities.